Evropski projekti kot dobra praksa zagotavljanja dostopnosti športa in rekreacije za invalide in starejše - Čanžar, Katja (Šport (Ljubljana), 2017)
Because of its vital effects on an individual and a society in general sport presents a fundamental right of each individual. Unfortunately, sports activities are not equally divided among all social categories. Since disabled sports participants and the elderly present a small share of sports participants and most sports public funding in Slovenia is provided by local communities, it is the role of municipalities to develop programmes for the previously mentioned categories. Reduction of lump-sum court fees for municipalities is in conflict with the needs of citizens also in the field of sport, which is characterised by fast and dynamic development. This is the reason why an example of good practice providing the disabled and the elderly access to sport and recreation in local communicities is introduced by use of European projects.
Keywords: Brežice; Brežice municipality; disabled; elderly; European projects; evropski projekti; invalidi; local community; lokalna skupnost; sport; starejši; šport